A 'proper' black mass: the rhetorical struggle over a deviant ritual. Issue 1 (2nd January 2021) - Laycock, Joseph P.
ABSTRACT: This article considers the rhetorical paradoxes surrounding The Satanic Temple (TST) and its interpretation of 'black mass' rituals. TST's conservative critics have framed the movement as part of an ancient tradition of Satanism while also claiming that its members are not Satanists at all but merely 'trolls' seeking to upset Christians. Catholic critics vehemently opposed TST's attempt to give a public performance of the black mass, but also accused TST of performing the black mass 'incorrectly' when TST explained it would not abuse a consecrated host. This article seeks to interpret these paradoxical responses by framing the black mass as a Christian discourse that TST has knowingly attempted to appropriate and repurpose. Drawing on David Frankfurter's theory of 'rituals of inversion', it argues that stories of black masses function to support certain Christian worldviews and that these worldviews are potentially weakened when their imagined inverted counterparts are appropriated. Thus, what is really at stake in debates surrounding TST's status as a Satanist movement is who can define an important site of discursive power within the Christian imaginaire .